High-laser-transmittance black glass fiber reinforced PBT composite material and preparation method thereof

By using rectangular cross-section glass fiber and compound black powder in black glass fiber reinforced PBT composite materials, combined with the compounding of PBT and PC, the problems of low laser transmittance and warping deformation of the material are solved, and high laser Balance of transmittance and strength.

CN119331394APending Publication Date: 2025-01-21QINGDAO GON TECH CO LTD

Patent Information

Application Number
CN202411355260.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing black glass fiber reinforced PBT composite materials have low laser transmittance during laser welding and are prone to warping and deformation, affecting the welding effect.

Method used

It uses rectangular cross-section glass fiber and compound black powder, combined with the compound of PBT and PC, to improve the laser transmittance and intensity of the material and reduce warping.

Benefits of technology

Significantly improves the laser transmittance of black glass fiber reinforced PBT composite materials, ensuring the strength and low warpage characteristics of the material, suitable for laser welding technology, and broadening material applications in the fields of new energy and photovoltaics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005063435470000071
    Figure BDA0005063435470000071
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and particularly relates to a high laser transmittance black glass fiber reinforced PBT composite material and a preparation method thereof, the high laser transmittance black glass fiber reinforced PBT composite material comprises, by weight, 35-46 parts of PBT resin, 10-25 parts of polycarbonate, 30 parts of rectangular cross section glass fiber, 0.2-0.6 part of a lubricant, 0.2-0.6 part of an antioxidant, 0.05-0.2 part of a transesterification inhibitor, and 0.1-0.5 part of black powder. The PBT resin, the polycarbonate, the lubricant, the antioxidant, the ester exchange inhibitor and the black powder are added into a high-speed stirrer according to the proportion to be mixed for 1-2 minutes, and a premix is obtained; and adding the premix into a double-screw extruder through a main hopper and a sanitary hopper, adding rectangular cross section glass fibers at a side feeding position, and carrying out melting, pelletizing and extrusion to obtain the black laser welding glass fiber reinforced PBT composite material. The flat glass fiber and the compound black powder are adopted, so that the light transmittance is remarkably improved, and meanwhile, the impact performance is improved through PC.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and particularly relates to a black glass fiber reinforced PBT composite material with high laser transmittance and a preparation method thereof. Background Art

[0002] Laser welding utilizes the excellent directionality and high power density of the laser beam to work. The laser beam is focused into a very small area through an optical system, forming a heat source area with highly concentrated energy at the weld in a very short time, thereby melting the welded material and forming a strong weld point and weld.

[0003] Compared with other traditional welding technologies, laser welding technology has the advantages of fast speed, large depth, and small deformation. In addition, the welding conditions are relatively wide and can be performed indoors or under any special conditions. In laser welding, the upper material needs to have the ability to project laser, and the upper material has a transmittance requirement during the manufacturing process (transmittance ≥ 25%). The lower material, on the contrary, needs to have the function of absorbing laser. The laser is absorbed and converted into heat in the light-absorbing layer. Finally, the upper and lower materials complete heat transfer under the action of the clamping force, expand and melt, and form a weld at the internal joint after cooling, thus forming a tight connection.

[0004] Laser welding can be widely used in materials such as polypropylene, polystyrene, polycarbonate, polyamide, acrylic, polyester, etc. However, there are some limitations. For example, when the two materials are black, the black material absorbs the laser energy, resulting in a small amount of laser light passing through, making it impossible to achieve welding. In addition, if the glass fiber material warps during the welding process, the two layers of material will not be in close contact, affecting the welding effect.

[0005] PBT is a semi-crystalline engineering plastic with advantages such as excellent electrical properties, solvent resistance and excellent processing performance, but it has disadvantages such as low notched impact strength and poor laser transmittance. As a milky white crystalline polymer, the laser transmittance of PBT is greatly reduced after being reinforced with glass fiber, especially the light transmittance of black materials is even worse. Polycarbonate (PC) is a non-crystalline plastic with advantages such as high notched impact strength and high transparency. The addition of PC can change the crystallization behavior of PBT material and inhibit the crystallization of PBT. The high toughness of PC can replace the toughening agent in the formula. Both PC and PBT are polyester materials with good compatibility. Taking the above points into consideration, adding PC resin to PBT can improve the light transmittance of laser.

[0006] Patent CN109233216B discloses a laser-weldable black glass fiber reinforced PBT composite material and its preparation method, including 31-46 parts of PBT resin; 10-20 parts of terephthalic acid and ethylene glycol ester copolymer and the like; 10-25 parts of polycarbonate; 20-30 parts of modified glass fiber; 1-3 parts of toughening agent; 1-3 parts of compatibilizer; 0.2-0.6 parts of lubricant; 0.2-0.6 parts of antioxidant; 0.05-0.2 parts of ester exchange inhibitor; 0.1-1.5 parts of black powder. This method requires the simultaneous addition of terephthalic acid and ethylene glycol ester copolymer and the like and polycarbonate to improve the light transmittance, and the glass fiber needs to be modified, which increases the complexity of the operation, and the notched impact strength of the PBT composite material obtained by this method is low, and it is difficult to take into account the tensile strength.

[0007] Therefore, it is necessary to provide an improved black glass fiber reinforced PBT composite material with high laser transmittance and a preparation method thereof to solve the above problems. Summary of the invention

[0008] The object of the present invention is to provide a black glass fiber reinforced PBT composite material with high laser transmittance and a preparation method thereof, so as to improve the laser transmittance of the PBT composite material while ensuring the strength of the PBT composite material.

[0009] To achieve the above-mentioned object, the present invention provides a black glass fiber reinforced PBT composite material with high laser transmittance, which comprises, by weight, 35-46 parts of PBT resin, 10-25 parts of polycarbonate, 30 parts of rectangular cross-section glass fiber, 0.2-0.6 parts of lubricant, 0.2-0.6 parts of antioxidant, 0.05-0.2 parts of ester exchange inhibitor and 0.1-0.5 parts of black powder.

[0010] Furthermore, the cross-sectional length of the rectangular cross-sectional glass fiber is 25 to 35 um, and the width is 6 to 10 um.

[0011] Furthermore, the cross-sectional length of the rectangular cross-sectional glass fiber is 30 um and the width is 8.2 um.

[0012] Furthermore, the black powder is composed of anthraquinone blue dye, perinone red dye, 5B green dye and transparent yellow 2G dye in a mass ratio of 1.25:1:0.85:0.85.

[0013] Furthermore, the viscosity of the PBT resin is 0.8-1.0 dL / g.

[0014] Furthermore, the molecular weight of the polycarbonate is 18000-25000 g / mol, and the melt index is 10-15 g / 10 min.

[0015] Furthermore, the transesterification inhibitor is sodium dihydrogen phosphate or sodium pyrophosphate; the lubricant is one of polyethylene wax and pentaerythritol stearate; and the antioxidant is at least one of phosphite and β-(3,5-di-tert-butyl-4-hydroxyphenyl).

[0016] The black glass fiber reinforced PBT composite material with high laser transmittance as described in any one of the above items comprises:

[0017] Add PBT resin, polycarbonate, lubricant, antioxidant, transesterification inhibitor and black powder into a high-speed mixer according to the proportion and mix for 1-2 minutes to obtain a premix;

[0018] The premix is ​​added into a twin-screw extruder through a main hopper, and rectangular cross-section glass fiber is added at a side feed point, and the premix is ​​melted, pelletized, and extruded to obtain a black laser-welded glass fiber reinforced PBT composite material.

[0019] Furthermore, the barrel temperature of the twin-screw extruder is 235° C.-240° C., the screw speed is 320 r / min, and the vacuum degree is -0.04 MPa.

[0020] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:

[0021] 1. The glass fiber reinforced PBT black material provided by the present invention has the characteristics of high laser transmittance and low warping as the upper material in laser welding. When the glass fiber diameter is low, the glass fiber's refraction effect on light is enhanced, resulting in more light being scattered, and the light transmittance is low. The rectangular glass fiber has a larger cross-sectional area. When the addition amount is the same, the rectangular glass fiber reinforced PBT has a higher transmittance. Moreover, the orientation of ordinary round glass fibers, the shrinkage in the flow direction and the vertical direction are inconsistent, and for glass fiber-added materials, the glass fiber orientation will be induced during the crystallization process of the material, so warping often occurs in the final injection molding stage, while rectangular glass fibers will reduce the occurrence of warping.

[0022] 2. The present invention eliminates the toughening agent and adopts PC with appropriate viscosity to ensure high toughness. Moreover, due to the good compatibility of PC, PBT and rectangular glass fiber, they can synergistically make up for the disadvantage of low impact strength of PBT while ensuring higher tensile strength. On the other hand, PC itself has good transparency and can inhibit PBT crystallization, thereby improving the overall laser transmittance.

[0023] 3. Compounding dyes with weak near-infrared light absorption, specifically anthraquinone blue dye: purple ring ketone red dye: 5B green dye: transparent yellow 2G dye in a ratio of 1.25:1:0.85:0.85, can improve laser transmittance while ensuring black appearance. And it has good light and heat stability.

[0024] The above key points can make up for the shortcomings of the products on the market today, so that black glass fiber reinforced PBT products can be better used in laser welding technology, while broadening the application of materials in new energy, photovoltaic and other fields. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0026] The invention provides a black glass fiber reinforced PBT composite material with high laser transmittance. The composite material comprises, by weight, 35-46 parts of PBT resin, 10-25 parts of polycarbonate, 30 parts of glass fiber with rectangular cross section, 0.2-0.6 parts of lubricant, 0.2-0.6 parts of antioxidant, 0.05-0.2 parts of ester exchange inhibitor and 0.1-0.5 parts of black powder.

[0027] PBT material has the characteristics of high strength and low notch impact. It is often necessary to add toughening agents during the modification process, and the toughening agent itself will also affect the laser transmittance of the material. PC, as a non-crystalline material, has high impact. The addition of PC can replace the toughening agent to a certain extent and reduce the impact of the toughening agent on laser transmittance. Moreover, PC and PBT are both polyester materials, which have good compatibility and are easy to process. Therefore, using PBT and PC as the main materials can ensure their strength and improve the transmittance at the same time. Combined with rectangular cross-section glass fiber, it can further play a reinforcing role, while reducing the scattering of light and improving the transmittance.

[0028] Furthermore, the cross-sectional length of the rectangular cross-sectional glass fiber is 25 to 35 um, and the width is 6 to 10 um.

[0029] Preferably, the cross-sectional length of the rectangular cross-sectional glass fiber is 30 um and the width is 8.2 um.

[0030] The black powder is composed of anthraquinone blue dye, violacetone red dye, 5B green dye and transparent yellow 2G dye in a mass ratio of 1.25:1:0.85:0.85. Ordinary carbon black or black masterbatch has light absorption, which makes it difficult for laser to penetrate, and is not suitable for use in laser welding materials. Dyes with weak near-infrared light absorption should be selected for color matching. Anthraquinones and violacetones of different colors are compounded in a certain proportion to obtain a color powder suitable for laser welding materials, and it has good light and heat stability.

[0031] Furthermore, the viscosity of the PBT resin is 0.8-1.0 dL / g.

[0032] Furthermore, the molecular weight of the polycarbonate is 18000-25000 g / mol, and the melt index is 10-15 g / 10 min.

[0033] Furthermore, the transesterification inhibitor is sodium dihydrogen phosphate or sodium pyrophosphate; the lubricant is one of polyethylene wax and pentaerythritol stearate; and the antioxidant is at least one of phosphite and β-(3,5-di-tert-butyl-4-hydroxyphenyl).

[0034] The black glass fiber reinforced PBT composite material with high laser transmittance as described in any one of the above items comprises:

[0035] Add PBT resin, polycarbonate, lubricant, antioxidant, transesterification inhibitor and black powder into a high-speed mixer according to the proportion and mix for 1-2 minutes to obtain a premix;

[0036] The premix is ​​added into a twin-screw extruder through a main hopper, and rectangular cross-section glass fiber is added at a side feed point, and the premix is ​​melted, pelletized, and extruded to obtain a black laser-welded glass fiber reinforced PBT composite material.

[0037] The barrel temperature of the twin-screw extruder is 235° C.-240° C., the screw speed is 320 r / min, and the vacuum degree is -0.04 MPa.

[0038] Examples 1-3 and Comparative Example 1

[0039] According to the proportions in Table 1, PBT resin, polycarbonate, lubricant, antioxidant, transesterification inhibitor and black powder were added into a high-speed mixer and mixed for 1-2 minutes to obtain a premix;

[0040] The premix is ​​added to the twin-screw extruder through the main hopper, and rectangular cross-section glass fiber is added at the side feed, and the black laser-welded glass fiber reinforced PBT composite material is obtained through melting, pelletizing and extrusion. The barrel temperature of the twin-screw extruder is 235℃-240℃, the screw speed is 320r / min, and the vacuum degree is -0.04MPa.

[0041] In Table 1, the glass fibers of Example 1 and Comparative Example 1 are ordinary glass fibers (single filament diameter 10um, short chopped length 3mm), and the glass fibers of Examples 2 and 3 are rectangular cross-section glass fibers of 30×8.2μm. The black powder of Comparative Example 1 is ordinary black powder (carbon black), and Examples 1-3 are compound black powders composed of anthraquinone blue dye, violaceous ketone red dye, 5B green dye and transparent yellow 2G dye in a mass ratio of 1.25:1:0.85:0.85. PBT resin is 0.83dL / g; polycarbonate molecular weight is 18000-25000g / mol, melt index is 10g / 10min; ester exchange inhibitor is sodium dihydrogen phosphate or; lubricant is polyethylene wax; antioxidant is phosphite.

[0042] Table 1 Formula of Examples 1-3 and Comparative Example 1

[0043] Sample Example 1 Example 2 Example 3 Comparative Example 1 PBT resin 49 49 54 49 Polycarbonate 20 20 15 20 Fiberglass 30 30 30 30 Lubricants 0.3 0.3 0.3 0.3 Antioxidants 0.3 0.3 0.3 0.3 Transesterification inhibitors 0.2 0.2 0.2 0.2 Black powder 0.2 0.2 0.2 0.2

[0044] Table 2 Performance test results of Examples 1-3 and Comparative Example 1

[0045]

[0046] It can be seen from Table 2 that the cantilever arm notched impact strength of the present invention is 13 kJ / m 2 When 0.2 parts of black powder are added, the near-infrared laser transmittance can also be maintained at a high level. This shows that the present invention ensures strength by compounding PBT and PC, and on this basis, significantly improves laser transmittance by rectangular glass fiber and compounding black powder.

[0047] Compared with comparative example 1, embodiment 1 differs in that the composite black powder is used, the laser transmittance is increased exponentially, and the strength performance does not fluctuate much.

[0048] Compared with Comparative Example 1, Example 2 uses rectangular glass fibers and compounded black powder, and the transmittance is significantly improved, and is higher than that of Example 1 using ordinary glass fibers. Rectangular glass fibers can both increase laser transmittance and reduce the degree of warping of the product. The mechanism is: when the diameter of the glass fiber is low, the refraction of the glass fiber on light is enhanced, resulting in more light being scattered and low light transmittance. The flat glass fiber has a larger cross-sectional area, and when the addition amount is the same, the flat glass fiber reinforced PBT has a higher transmittance. Moreover, the orientation of ordinary round glass fibers, the shrinkage in the flow direction and the vertical direction are inconsistent, and for fiber-reinforced materials, the orientation of the glass fibers will be induced during the crystallization process of the material, so warping often occurs in the final injection molding stage, while flat glass fibers will reduce warping.

[0049] Example 3 Compared with Example 2, the proportion of PC was adjusted. It was found that the infrared laser transmittance of 20 parts of PC was significantly higher than that of 15 parts of PC, and the impact performance was improved by 1 kJ / m 2about.

[0050] In summary, the transmittance of near-infrared light can be effectively improved by improving the type of glass fiber, black powder and the amount of PC added. This achievement can effectively solve the problem of low laser transmittance of black glass fiber reinforced PBT.

[0051] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A black glass fiber reinforced PBT composite material with high laser transmittance, characterized in that: The invention comprises, by weight, 35-46 parts of PBT resin, 10-25 parts of polycarbonate, 30 parts of rectangular cross-section glass fiber, 0.2-0.6 parts of lubricant, 0.2-0.6 parts of antioxidant, 0.05-0.2 parts of ester exchange inhibitor and 0.1-0.5 parts of black powder.

2. The black glass fiber reinforced PBT composite material with high laser transmittance according to claim 1, characterized in that: The cross-sectional length of the rectangular cross-sectional glass fiber is 25 to 35 um, and the width is 6 to 10 um.

3. The black glass fiber reinforced PBT composite material with high laser transmittance according to claim 2, characterized in that: The cross-sectional length of the rectangular cross-sectional glass fiber is 30 um, and the width is 8.2 um.

4. The black glass fiber reinforced PBT composite material with high laser transmittance according to claim 1, characterized in that: The black powder is composed of anthraquinone blue dye, perinone red dye, 5B green dye and transparent yellow 2G dye in a mass ratio of 1.25:1:0.85:0.

85.

5. The black glass fiber reinforced PBT composite material with high laser transmittance according to claim 1, characterized in that: The viscosity of the PBT resin is 0.8-1.0 dL / g.

6. The black glass fiber reinforced PBT composite material with high laser transmittance according to claim 1, characterized in that: The molecular weight of the polycarbonate is 18000-25000 g / mol, and the melt index is 10-15 g / 10 min.

7. The black glass fiber reinforced PBT composite material with high laser transmittance according to claim 1, characterized in that: The transesterification inhibitor is sodium dihydrogen phosphate or sodium pyrophosphate; the lubricant is one of polyethylene wax and pentaerythritol stearate; and the antioxidant is at least one of phosphite and β-(3,5-di-tert-butyl-4-hydroxyphenyl).

8. A black glass fiber reinforced PBT composite material with high laser transmittance according to any one of claims 1 to 7, characterized in that: include: Add PBT resin, polycarbonate, lubricant, antioxidant, transesterification inhibitor and black powder into a high-speed mixer according to the proportion and mix for 1-2 minutes to obtain a premix; The premix is ​​added into a twin-screw extruder through a main hopper, and rectangular cross-section glass fiber is added at a side feed point, and the premix is ​​melted, pelletized, and extruded to obtain a black laser-welded glass fiber reinforced PBT composite material.

9. The black glass fiber reinforced PBT composite material with high laser transmittance according to claim 8, characterized in that: The barrel temperature of the twin-screw extruder is 235° C.-240° C., the screw speed is 320 r / min, and the vacuum degree is -0.04 MPa.

Citation Information

Patent Citations

  • A laser-weldable black glass fiber reinforced PBT composite material and its preparation method

    CN109233216B

Cited By

  • Light-transmitting laser-weldable glass fiber reinforced PBT (Polybutylene Terephthalate) material and preparation method thereof

    CN120271970A

  • Light-transmitting laser-weldable glass fiber reinforced pbt material and method for producing the same

    CN120271970B

  • High-transmittance laser welding reinforced PC / PBT composite material and preparation method thereof

    CN121108691A